Molecular variability of Hemileia vastratix Berk. & Br. in two Venezuelan states based on RAPD and REMAP markers (Bioagro, 2025)
Coffee leaf rust, caused by Hemileia vastratix Berk. and Br. (Hv), is economically the most important disease of this crop worldwide. More than 50 physiological races have been identified, which indicate its genetic diversity, due to either by genetic mutations or by the presence of transposable genes. In this study, a total of 21 isolates of the fungus were characterized using RAPD and REMAP markers between the two techniques, including race XXXIX, two pathotypes Hv01ve and Hv02ve, which were previously identified for Venezuela, and three control isolates (Rz II, Rz XXXIII and Hv05) from Brazil. Isolates were collected in the states of Lara and Táchira.  After DNA extraction, RAPD was performed using twenty six primers of the OPA, OPB, OPC, OPD, OPE, OPF, OPG, OPH, OPK, OPL, OPM, OPN, OPO  and OPP series; and REMAP with five combinations LTR/ISSR (48F/D1C, 48R/D1C, 48R/T1C, 81F/D1C and 81F/T1C), using standard protocols. Statistical analysis was realized using the Infogen program. Results showed that 92.11% of RAPD and 96.55% of REMAP amplified bands were polymorphic and its information (PIC) varied from 0.15 to 0.32, which suggests a high genetic diversity among the Hv isolates. In addition, in both markers three groups were formed, discriminated by geographic distribution and altitude.
Keywords: Coffee rust; geographic zoning